2020
DOI: 10.1111/asj.13443
|View full text |Cite
|
Sign up to set email alerts
|

Breed differences in macrophage infiltration and senescence state in adipose tissues of Wagyu and Holsteins

Abstract: Obesity stimulates the macrophage infiltration and senescence state in adipose tissues of humans and rodents. The adipogenesis capacity of Japanese Black cattle (Wagyu) is higher than that of Holsteins. We hypothesized that breed differences between Wagyu and Holsteins may affect the level of macrophage infiltration and senescence state in adipose tissues. The macrophage infiltration, senescence marker gene expression and activity of senescence-associated β-galactosidase (SA-βgal) in visceral and intramuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…We showed that the intramuscular adipocyte size of Holstein was smaller than that of Wagyu. We also showed that the expression of adiponectin gene in the intramuscular adipose tissue of Holstein was higher than that of Wagyu (Yamada et al, 2020a). Adipose tissue macrophages are key mediators of insulin resistance in humans and rodents (Russo & Lumeng, 2018).…”
Section: Macrophage Infiltration: Breed Differencesmentioning
confidence: 85%
See 4 more Smart Citations
“…We showed that the intramuscular adipocyte size of Holstein was smaller than that of Wagyu. We also showed that the expression of adiponectin gene in the intramuscular adipose tissue of Holstein was higher than that of Wagyu (Yamada et al, 2020a). Adipose tissue macrophages are key mediators of insulin resistance in humans and rodents (Russo & Lumeng, 2018).…”
Section: Macrophage Infiltration: Breed Differencesmentioning
confidence: 85%
“…We showed that macrophage infiltration in visceral adipose tissue of Wagyu was higher than that of Holsteins (Yamada et al, 2020a). In contrast, there was no difference in macrophage infiltration in subcutaneous adipose tissue between Wagyu and Holsteins.…”
Section: Macrophage Infiltration: Breed Differencesmentioning
confidence: 96%
See 3 more Smart Citations